Orbitopatia jako manifestacja choroby IgG4-zależnej - opis przypadków = Orbitopathy as a manifestation of IgG4-related disease - case report - Zwolak, Agnieszka; Malicka, Joanna; Zwolak, Robert; Dudzińska, Marta; Świrska, Joanna; Daniluk, Jadwiga; Tarach, Jerzy; Łuczyk, Robert (Journal of Education, Health and Sport, 2016)
Zwolak Agnieszka, Malicka Joanna, Zwolak Robert, Dudzińska Marta, Świrska Joanna, Daniluk Jadwiga, Tarach Jerzy S., Łuczyk Robert. Orbitopatia jako manifestacja choroby IgG4-zależnej - opis przypadków = Orbitopathy as a manifestation of IgG4-related disease - case report. Journal of Education, Health and Sport. 2016;6(12):475-487. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.208373 http://ojs.ukw.edu.pl/index.php/johs/article/view/4078 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 754 (09.12.2016). 754 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 01.12.2016. Revised 12.12.2016. Accepted: 19.12.2016. Orbitopatia jako manifestacja choroby IgG4-zależnej - opis przypadków Orbitopathy as a manifestation of IgG4-related disease - case report Agnieszka Zwolak1,2, Joanna Malicka2, Robert Zwolak3, Marta Dudzińska1, Joanna Świrska1,2, Jadwiga Daniluk1,4, Jerzy S. Tarach2, Robert Łuczyk1 1Katedra Interny z Zakładem Pielęgniarstwa Internistycznego, Uniwersytet Medyczny w Lublinie 1Chair of Internal Medicine and Department of Internal Medicine in Nursing, Medical University of Lublin 2Klinika Endokrynologii, Uniwersytet Medyczny w Lublinie 2Department of Endocrinology, Medical University of Lublin 3Klinika Reumatologii i Układowych Chorób Tkanki Łącznej 3Department of Rheumatology and Connective Tissue Diseases 4Instytut Zdrowia, Państwowa Szkoła Wyższa im Papieża Jana Pawła II w Białej Podlaskiej 4Instiutute of Public Health, State School of Higher Education in Biała Podlaska Streszczenie Wstęp: Choroby IgG4-zależne stanowią multidyscyplinarny problem, ich istotą są nacieki z komórek plazmatycznych z towarzyszącym włóknieniem zajętych tkanek, a tym tkanek oczodołu. Celem badania jest przedstawienie dwóch przypadków pacjentów z orbitopatią IgG4. Materiał i metody: Analizy dokonano w oparciu o dokumentację medyczną pacjentów Przypadek 1: 68-mężczyzna został przyjęty do poradni endokrynologicznej z powodu narastającego wytrzeszczu obu gałek ocznych. Badanie MRI potwierdziło powiększenie i obrzęk wszystkich mięśni okoruchowych. Inne choroby, w przebiegu których dochodzić może do orbitopatii, w tym choroba Graves’a, zostały wykluczone. W oparciu o podwyższony poziom przeciwciał IgG4 w surowicy krwi, rozpoznano chorobę IgG4-zależną. Rozpoczęto leczenie glikokortykosteroidami, w wyniku czego doszło do znacznej regresji zmian w oczodołach. Leczenie powtórzono po upływie roku z powodu nawrotu objawów, z następowym leczeniem metotreksatem. Do chwili obecnej pacjent pozostaje w całkowitej remisji klinicznej, kontynuuje leczenie metotreksatem z dobrą tolerancją. Przypadek 2: 62-letnia kobieta, z chorobą Graves’a, po operacji usunięcia guza z prawego oczodołu (hist-pat: sclerosing inflammatory pseudotumor), została przyjęta do Kliniki Endokrynologii z powodu nawrotu wytrzeszczu oka prawego. Wykluczono orbitopatię w przebiegu choroby Graves’a. Na podstawie podwyższonego poziomu przeciwciał IgG4 w surowicy oraz obrazu histopatologicznego usuniętej uprzednio zmiany oczodołu rozpoznano chorobę IgG4-zależną. Rozpoczęto leczenie glikokortykosteroidami, z następową terapią metotrexatem oraz azatiopryną. Pacjentka do chwili obecnej pozostaje w remisji choroby. Wnioski: W przypadku cech orbitopatii w diagnostyce różnicowej należy brać pod uwagę możliwość rzadko występującej patologii, jaką są choroby IgG4- zależne. Słowa kluczowe: choroby IgG4-zależne, orbitopatia, glikokortykosteroidy Abstract Introduction: Immunoglobulin-G4-related disease (IgG4-RD) is a multidisciplinary problem due to plasmatic cells infiltration and areas of fibrosis in the affected tissues, including the eye. The aim of the study was to present two patients with orbitopathy due to IgG4-related eye disease. Material and methods: Analysis of medical records of patients. Case 1: A 68-year old man, was admitted to the endocrinology clinic because of increased protrusion of both eyeballs. The MRI scans revealed enlargement and swallowing of all periorbital muscles. Common diseases of the eyeballs, including Graves disease were excluded. Based on elevated serum IgG4, IgG4-related disease was stated. The glicocorticosteroid therapy was introduced. Evident regression of protrusion of eyeballs was observed. The therapy was repeated one year later because of recurrence of symptoms and methotrexate therapy was added to this. The patient continues now methotrexate therapy only and does not present any symptoms of orbitopathy. Case 2: A 62-years old woman with Graves disease, after surgery of the tumor of the right orbit, was admitted to the Endocrinology Clinic because of right eye protrusion rebound. The Graves orbitopathy was ruled out. Since IgG4 level in plasma was elevated and considering histopathological recognition of the removed tumor of the orbit (sclerosing inflammatory pseudotumor), IgG4-related disease of the eye was stated. Glucocorticosteroids were introduced, followed by methotrexate and azathioprine therapy. The patient remains in remission now. Conclusion: Presented cases highlight the importance of considering IgG4-RD in the differential diagnosis of orbitopathy. Key word: IgG4-related disease, orbitopathy, glucocorticosteroids